Pengaruh Kualitas Pelayanan Islami Terhadap Kepuasan dan Loyalitas Nasabah Bank BRI Syariah Surabaya - Rizky Pratama Putra; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to determine the influence of the Islamic service quality on customer satisfaction and loyalty switching intentions moderated by religious knowledge level in in Customer of BRISyariah Bank in Surabaya.The research method used is quantitative approach. This research use a total of 96 customers of BRISyariah Surabaya. Customer characteristics used are Moslem, registered as a funding or deposit customer for at least a year. The sampling technique is purposive sampling. This research uses a method PLS (Partial Least Square).The results showed that Islamic service quality has a positive and significant impact on customer satisfaction. Other results showed that customer satisfaction has significant impact to customer loyalty and Islamic service quality has significant effect on customer loyalty. This results in accordance with the theory of Othman and Owen that CARTER could be used to measure the quality of service on Islamic Banking. Suggestion for the BRISyariah Bank in Surabaya should maintain and improve its service quality in order to improve satisfaction and form a loyal customer. For further research, can be done by adding another variable which affect customer satisfaction and loyalty. REFERENCES Al Qur’an dan Terjemahannya. 2005. Syamil Al Qur’an. Bandung: PT. Syaamil Cipta Media.Abedniya, A., Zaeim, M.N. (2011). “Measuring the Perceive Service Quality in the Islamic Banking System in Malaysia”. International Journal of Business and Social Science. Vol. 2, No. 13.Anshori, Muslich dan Sri Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Astuti, S.P., Wilasari, W., Utami, D.E. (2009). “Meningkatkan Kualitas Pelayanan Di Bank Syariah”. Jurnal Manajemen Bisnis. Vol. 2, No. 1, h: 47-58.Badara, S.B., Nik Mat, N.K., Mujtaba, A.B., Al-Refai, A.N., Badara, A.M., Abubakar, F.M. (2013). “Direct Effect of Service Quality Dimensions on Customer Satisfaction and Customer Loyalty in Nigerian Islamic Bank”. Management 2013. 3 (1): 6- 11.Dick, A., Basu K., (1994). “Customer Loyalty: Towards an integrated framework”. Journal of the Academy of Marketing Science, 22 (2), 99-113.Ghozali, Imam. 2008. Structural Equation Modeling Metode Alternatif dengan Partial Least Square. Semarang: BP UNDIP.----------, Imam. 2011. Structural Equation Modeling Metode Alternatif Dengan Partial Least Square PLS. Semarang: BP UNDIP.Ishak, A., Luthfi, Z. (2011). “Pengaruh Kepuasan Dan Kepercayaan Konsumen Terhadap Loyalitas: Studi Tentang Peran Mediasi Switching Cost”. Siasat Bisnis. Vol. 15, h: 55-66.Jones, Thomas, W. E. Sasser. (1994). “Why Satisfied Customers Defect”. Harvard Business Review, 73 (November-December), 88-99.Kertajaya, Hermawan dan Syakir Sula. 2006. Syariah Marketing. Bandung: Mizan Media Utama.Kotler, Philip dan Kevin Keller. 2009. Manajemen Pemasaran, Edisi Ketiga Belas. Jakarta: Erlangga.Mohsan, Faizan, et al. (2011). “Impact of Customer Satisfaction on Customer Loyalty and Intentions to Switch: Evidence from Banking Sector of Pakistan”. International Journal of Business and Social Science. Vol. 2 No. 16.Nazir, Moh. 2005. Metode Penelitian. Bogor: Ghalia Indonesia.Osman, I., Ali, H., Zainuddin, A., Rashid, W.E., Jusoff, K. (2009). “Customers Satisfaction in Malaysian Islamic Banking”. International Journal of Economics and Finance. Vol. 1, No. 1.Oliver, Richard. (1997). ”Satisfaction: Behavioral Perspective on the Consumer”. Mc Graw-Hill. International editions.--------, Richard. (1999). “Whence Consumer Loyalty?” Journal of Marketing. Vol. 63 (Special Issue 1999), 33-44.Parasuraman, A., Zeithaml, V.A. & Berry, L.L. (1985). “A Conceptual Model of Service Quality and Its Imlications for Future Research”. Journal of Marketing. Vol. 49, 41-50.Peter, Paul dan Jerry Olson. 2002. Consumer Behavior : Perilaku Konsumen dan Strategi Pemasaran. Jakarta : Erlangga.Priyanti, D.R. (2005). Analisis Mutu Pelayanan Di Bank Syariah (Studi Kasus Pada Unit Usaha Syariah – Bank Permata). Tesis Program Magister Manajemen, Universitas Gunadarma: tidak diterbitkan.Rachmawati, R. (2010). “Pengaruh Kepuasan Terhadap Loyalitas Pelanggan (Sebuah Kajian Terhadap Bisnis Makanan)”. TEKNUBUGA. Volume 2 No. 2. Rianto, Nur. 2010. Dasar-Dasar Pemasaran Bank Syariah. Bandung: Alfabeta.Rust , R.T., Zahorik, A.J. (1993). “Customer Satisfaction, Customer Retention and Market Share”. Journal of Retailing, 69, 193-215.Saeed, M., Ahmad, Z.U and Mukhtar, S.M. 2001. “International Marketing Ethics from an Islamic Perspectives: A Value Maximization Approach”, Journal of Business Ethics, 32: 127- 142; Salesperson Selling Behaviors on Customer Satisfaction with Products.” Journal of Retailing, 73(2): 171-183.Sugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Tjiptono, Fandy. 1996. Prinsip-Prinsip Total Quality Service (TQS). Yogyakarta: Andi Offset.------------, Fandy dan Anastasia Diana. 2001. Total Quality Management (TQM). Yogyakarta: Andi Offset.Wijaya, Tony. 2011. Manajemen Kualitas Jasa. Jakarta: Indeks. www.bi.go.id www.brisyariah.co.idYamin, Sofyan dan Heri Kurniawan. 2011. Partial Least Square Path Modeling. Bandung: Salemba Infotek.Zainuddin, Muhamad. 2000. Metodologi Penelitian. Surabaya: BP AIRLANGGA.Zeithaml, V. A., and Marry Jo Bitner. 2000. Services Marketing: Integrating Customer Focus Across the Firm. Second Edition. Boston: Irwin McGraw-Hill, Inc.------------, V. A., Parasuraman, A., & Malhotra, A. 2000. E-service quality: Definition, dimensions and conceptual model. Working paper. Cambridge, MA: Marketing Science Institute.